Persuasion in the use of functional and ideological strategies in Trump and Clinton's 2016 presidential debates - Yaseen, Ahmed Hasani (2020)
Studies on political debates have mainly emphasised on critical discourse analysis (CDA) as a means of analysing the politicians' speeches. This study explores the functional and ideological strategies used by Hillary Clinton and her rival Donald Trump in the presidential debates (PDs) of the U.S. 2016. The study adopts Benoit's (2007) functional theory and van Dijk's (2000a) ideological strategies for its analytical framework. However, rare previous studies have investigated PDs from the U.S. presidential election campaign using Benoit functional theory combined with van Dijk ideological strategies in addition to the Critical Discourse Analysis method. And scarce studies deal with ideology and/or persuasion in the U.S. 2016 PDs. Studies that exist paid no attention to how ideological and functional strategies could appeal and persuade the audience. The current study is analysing functions and ideologies which the PCs used as ways to persuade the audience. Also, it looks at which of the ideological strategies used that overlap with the functional categories in order to further see the strategies within the functions. Hence, by looking at these overlaps and marking the types of strategies used in tandem with the functions, one can perhaps assume how each PC attempts to persuade and convince the audience. The research objectives of this study aim to, first, determine the ideological strategies used under the functional strategies that are utilised by Trump and Clinton in the U.S. 2016 PDs; second, analyse the functional strategies (i.e. acclaim, attack, and defence that are based on topics) which are used by both presidential candidates (PCs) to persuade the voters. Third, it seeks to compare Trump and Clinton’s use of ideological and functional strategies in relation to persuasion; fourth, explain the prominent role of Trump and Clinton's presidential debates in shaping their preferability as best candidate for a president to the voters. Data was collected from The Times New York website, and a qualitative approach is adopted in analysing the data using ATLAS.ti.7 software programme. The findings revealed, after drawing a comparison to the strategies used by both PCs, that the dominant ideological strategies are: interaction and context, negative other-presentation, vagueness, generalisation, polarisation, populism, actor description, number game, positive self-presentation, disclaimers, repetition, and norm expression. In addition, the functional strategies that are used by Trump and Clinton are attack, acclaim, and defence based on policy and character. In relation to the PCs, these strategies, according to Benoit (2007), represent one of the keys that can be used in winning the election campaign, because the voters may be persuaded by the PC who uses these strategies efficiently compared to the rival. The findings of the study show that the voters may be persuaded by the ideological and functional strategies used by both PCs, and they would vote for the most suitable PC. Also, the findings indicate that the sequence of using the functional strategies, which is attack, acclaim, defence, differ from that stated in Benoit's (2007) functional theory (acclaim, attack, defence). That is, the findings that concern with Benoit's functional theory reveal that this theory needs some improvements to address the use of the strategy of attack rather than acclaim as observed in the U.S. 2016 PDs.